Odpowiedzi

Najlepsza Odpowiedź!
2009-10-07T19:23:36+02:00
A) 2x(y-x) = 2xy-2x²
b) -4y(y-2x)=-4y²+8xy
c) 3x(2xy+3x)=6x²y+9x²
d) 3m(4+5p-2q)=12m+15mp-6mq
e) -5x(x-2y+2)=-5x²+10xy-10x
f) -4a(-5a+5ab-3b)=20a²-20a²b+12ab
  • Użytkownik Zadane
2009-10-07T19:27:27+02:00
A) 2x(y-x)=2xy-2x²
b) -4y(y-2x)=-4y²+8xy
c) 3x(2xy+3x)=6x²y+9x²
d) 3m(4+5p-2q)=12m+15mp-6mq
e) -5x(x-2y+2)=-5x²+10xy-10x
f) -4a(-5a+5ab-3b)=20a²-20a²b+12ab
2009-10-07T19:32:16+02:00
A) 2x(y-x) = 2xy-2x^2
b) -4y(y-2x) = -4y^2+8xy
c) 3x(2xy+3x) = 3x^2 y+9x^2 = 12x^2 y
d) 3m(4+5p-2q) = 12m+12mp-6mq
e) -5x(x-2y+2) = -5x^2 + 10xy - 10x
f) -4a(-5a+5ab-3b) = 20a^2-20a^2b+12ab